10z-(3z-7)=17

Simple and best practice solution for 10z-(3z-7)=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z-(3z-7)=17 equation:


Simplifying
10z + -1(3z + -7) = 17

Reorder the terms:
10z + -1(-7 + 3z) = 17
10z + (-7 * -1 + 3z * -1) = 17
10z + (7 + -3z) = 17

Reorder the terms:
7 + 10z + -3z = 17

Combine like terms: 10z + -3z = 7z
7 + 7z = 17

Solving
7 + 7z = 17

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 7z = 17 + -7

Combine like terms: 7 + -7 = 0
0 + 7z = 17 + -7
7z = 17 + -7

Combine like terms: 17 + -7 = 10
7z = 10

Divide each side by '7'.
z = 1.428571429

Simplifying
z = 1.428571429

See similar equations:

| -2(x-3)+4x+8=3(4-3x)+12x-9 | | -4*3/17 | | 7x-15=4x+13 | | 0.30x+0.20(150)=0.15(110) | | Ac=7x-15 | | 5x-7+10x-8=180 | | x^2+24x+320=0 | | W=-0.5v | | x-(x-4)=8 | | -6=17+x | | .5x+10=14.5 | | 3x+y=2x+33 | | 3/2(x-4)=7/6 | | lny+10y-4=0 | | 2x=3x-45 | | 10+5(z-2)=-2z+2 | | (x+20)(x-6)(13x+7)= | | 2/3=8W | | -4.2x+3.5y+2.6-5.9x-2.4y= | | 10+5z(z-2)=-2z+2 | | 2w=4/3 | | x^2-4=8x | | 5k+20-3-3k=7k | | -5/(-2)=x | | .8(x+20)+.2x=41 | | 178.7-176.9= | | 2(x+2)-9=3x-19 | | 15x+y+.25z=100 | | 2*3+4-36= | | 10x+18y=700 | | (1/3)9.9.9 | | 4(x+1)+(2x-7)=50 |

Equations solver categories